Effectiveness of prophylaxis treatment in the acute febrile stage of febrile seizure in children under five years old - Fayyazi, Afshin; pezeshki, Nasrollah; Hosseini, Firoozeh; Eslamian, Reyhane; Esnaashari, Farzaneh (Iranian Journal of Child Neurology, 2022)
Abstract Objectives In children suffering from febrile seizure, the likelihood of recurrence seems to be high in the early hours following the first episodes in the absence of proper interventions. The present study was aimed at assessing and comparing the outcomes of different preventive interventions in the acute stage after febrile seizure in children. Materials & Methods This randomized clinical trial study was performed between September 2015 and September 2016. We enrolled patients aged between 6 and 60 months suffered from febrile seizure and referred to the Pediatric Emergency Department at Besat Hospital in Hamadan. The eligible patients were randomly assigned to the following four receive one of the following groups: group 1 (not receiving any anti-seizure drugs), group 2 (receiving a single dose of phenobarbital) on admission, group 3 (receiving a single dose of phenobarbital on admission continued until the fever is resolved), and group 4 (receiving diazepam until the disappearance offever). Results The study population consisted of 248 children. The recurrence rate of seizure in the acute stage was 4.84%. Also, the impact of diazepam and phenobarbital (either as a single dose or as continuous) on the prevention of febrile seizure recurrence in the acute stage has been established. None of the patients had febrile status epilepticus. Conclusion Controlling seizures without prescribing anti-seizure drugs increases the risk for the recurrence of febrile seizure in the acute stage. Different drug regimens for controlling seizure, including diazepam and phenobarbital (as stat or maintenance), may play a similar role in preventing the occurrence of febrile seizure